Impact of Age on Patient-Reported Outcome Measures in Total Knee Arthroplasty - Townsend, Luke A.; Roubion, Ryan C.; Bourgeois, Devin M.; Leonardi, Claudia; Fox, Rabun S.; Dasa, Vinod; Pollock, Grant R. (The Journal of Knee Surgery, 2018)
Patient expectations and demographics are vital factors in determining patient satisfaction and outcomes from total knee arthroplasty (TKA). This study was a retrospective chart review that analyzed data from TKA patients to determine the impact of age on patient-reported outcomes measures following TKA. Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Oxford knee scores were collected as primary outcome measures from 356 consecutive patients who underwent TKA. Oxford knee scores were further divided into pain and function subscores. Patients were age categorized as <50, 50 to 59, 60 to 69, 70 to 79, and >79. Preoperative scores were compared among age categories including age category, gender, body mass index (BMI), and length of stay (LOS) in the model as fixed effects. Scores collected postoperatively (∼10, 30, 90, and 180 days postoperation) were analyzed as repeated measures including age category, day and their interaction, gender, BMI, LOS, and preoperative score in the model. Preoperative OXFORD scores significantly differed among age categories (p < 0.05) and were numerically higher for the older (≥60 years old) compared with younger patients (<60 years old). After adjusting for preoperative scores, postoperative WOMAC and overall, pain, and function OXFORD scores significantly differed among the age groups (p < 0.05), with patients younger than 60 years reporting the worst scores in the postoperative time period. Older patients reported better preoperative overall, pain, and function scores and greater post-TKA outcomes than younger patients. A better understanding of factors that influence patient-reported outcomes can help providers to better manage patient expectations.
Keywords: total knee arthroplasty; outcomes; age; pain; function